Development Of Soft And Flexible Filament For 3D Printing Of Anatomical Model - Ismail, Iman Firdaus (Universiti Sains Malaysia, 2022)
Flexible filaments have been widely used in additive manufacturing to produce soft models, such as the human brain model. Due to its better stability, thermoplastic polyurethane (TPU) filament is commonly used in this part. It has soft and hard segments, which can provide the best properties in terms of flexibility but are higher in cost for every filament. The polymer blend approach was used in TPU, adding rubber to enhance flexibility and reduce cost. This study aims to produce flexible filament from polymer blending used for 3D printed anatomical models using customized soft 3D printing. Two types of rubber are used for the second component, ethylene propylene diene monomer (EPDM) and styrene butadiene rubber (SBR) compounds. For material processing, the blending of 75%TPU/ 25%EPDM and 75%TPU/ 25%SBR was successfully fabricated using an internal mixer and extruded into filament using a single screw extruder. The dumbbell shape for the characterization and human brain model was then printed using a 3D printer. It was found that both blendings could be extruded and formed into flexible shapes and could be printed into brain anatomy models. Still, the properties of the materials were greatly affected by rubber types and compositions of the added fillers. The blending of TPU95A/EPDM is preferred for fabricating anatomical models due to its better toughness and good stability, and higher physical crosslink density due to the interaction of linear ethylene propylene diene with the soft segment of TPU itself. In addition, the adhesion studies are conducted, and 35mm/min printing speed enhance the mechanical properties.